From in vitro towards in situ: structure‐based investigation of ABC exporters by electron paramagnetic resonance spectroscopy. Issue 23 (1st December 2020) - Bordignon, Enrica; Seeger, Markus A.; Galazzo, Laura; Meier, Gianmarco
Abstract : ATP‐binding cassette (ABC) exporters have been studied now for more than four decades, and recent structural investigation has produced a large number of protein database entries. Yet, important questions about how ABC exporters function at the molecular level remain debated, such as which are the molecular recognition hotspots and the allosteric couplings dynamically regulating the communication between the catalytic cycle and the export of substrates. This conundrum mainly arises from technical limitations confining all research to in vitro analysis of ABC transporters in detergent solutions or embedded in membrane‐mimicking environments. Therefore, a largely unanswered question is how ABC exporters operate in situ, namely in the native membrane context of a metabolically active cell. This review focuses on novel mechanistic insights into type I ABC exporters gained through a unique combination of structure determination, biochemical characterization, generation of conformation‐specific nanobodies/sybodies and double electron–electron resonance. Abstract :